The Mistake on Regulatory Criminal Elements: The Case Of The "Usurpation of plant breeders" (306 C.P.) (2015)
This article presents an analysis of the criminal offence of Usurpation of plant breeders’ rights –PBR- (Sect. 306 CP), whose legal definition contains a specific kind of normative terms, namely, theoretical or cognitive or specialized technical element.